Idiolektostylem w mur, czyli o idiolekcie, idiostylu i krytycznej analizie dyskursu – na przykładzie felietonów Krzysztofa Skiby w tygodniku „Wprost” - Kudra, Andrzej (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
The author ponders the issue of idiolect from a theoretical perspective, which cannot be done without taking a textual example into consideration. “Text filter” is central to idiolect studies. It is not possible to restrict studies only to language system research; it is necessary to address axiological issues and to treat the language in a holistic way. For that reason, in the case of an idiolect, it would be more adequate to talk about an idiostyle and, better still, about an idiolectostyle.